2015
DOI: 10.4085/1062-6050-49.6.01
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow After Exercise-Induced Muscle Damage

Abstract: Context:The most common modality used to address acute inflammation is cryotherapy. Whereas pain decreases with cryotherapy, evidence that changes occur in perfusion of skeletal muscle is limited. We do not know whether ice attenuates the increases in perfusion associated with acute inflammation.Objective: To examine the effects of repeated applications of ice bags on perfusion of the gastrocnemius muscle after an eccentric exercise protocol.Design: Controlled laboratory study. Setting: Laboratory.Patients or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…We studied highly trained athletes; however, the effects of CWI can last longer in athletes who train at lower levels. In healthy individuals, Selkow et al 12 observed less perceived pain 48 hours after CWI. Given that our results provided evidence of a positive effect of CWI on serum LDH levels, muscle soreness, and upper and lower body performance until 24 hours, this approach can be useful when athletes are submitted to periods of intensified training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied highly trained athletes; however, the effects of CWI can last longer in athletes who train at lower levels. In healthy individuals, Selkow et al 12 observed less perceived pain 48 hours after CWI. Given that our results provided evidence of a positive effect of CWI on serum LDH levels, muscle soreness, and upper and lower body performance until 24 hours, this approach can be useful when athletes are submitted to periods of intensified training.…”
Section: Discussionmentioning
confidence: 99%
“…These peripheral changes from the low temperature of the liquid medium result in less muscle soreness signaling. 31 Whereas the analgesic effect of CWI has not been fully explained, 12 investigators 32 believe that the smaller nerve conduction decreases the firing rate of the muscle spindle and afferent responses, thereby decreasing pain and spasm. Yanagisawa et al 33 observed that cryotherapy increases intracellular pH, delaying the onset of muscle edema, but other physiologic effects, such as the release of interleukin-6, can occur in the muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There continues to be widespread use of cryotherapy techniques postexercise despite inconsistencies in the literature validating its effectiveness. Cryotherapy decreases the tissue metabolic rate, 14 promotes superficial vasoconstriction, 15 decreases vascular permeability, 16 and leads to less edema formation. 12,17 A form of cryotherapy, cold-water immersion therapy has an additional effect, due to hydrostatic pressure, at encouraging reabsorption of interstitial fluids found in the muscle after exercise.…”
Section: Best Evidencementioning
confidence: 99%
“…One text 11 even went so far as to recommend treatment times. A number of researchers [13][14][15][16][17][18][19][20][21][22][23][24] have incorporated cooling recommendations based on subcutaneous tissue thickness into their study designs or accounted for subcutaneous tissue thickness in different results across patients. Textbooks and scholarly articles suggested translating these recommendations to patient care, but many clinicians were complacent and relied on a ''cookbook approach'' to patient care.…”
mentioning
confidence: 99%